1989
DOI: 10.1111/j.1469-8137.1989.tb04211.x
|View full text |Cite
|
Sign up to set email alerts
|

Catabolism of chlorophyll in vivo: significance of polar chlorophyll catabolites in a non‐yellowing senescence mutant of Festuca pratensis Huds.

Abstract: S U M M A R -i'During dark incubation of excised leaf tissue from Bf 993, a senescence mutant o( Festuca pratensis Huds., a highly polar green pigment fraction (PC) increased from negligible amounts at day 0 to maximal concentrations at days 4-6 and declined thereafter. Over the same time-scale, chlorophyll (chl) was lost from leaves of the normal genotype Rossa without any detectable accumulation of PC. Chromatographic analysis established that PCs are a group of dephytylated derivatives of chl a. Chl protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…In the normal, yellowing genot\-pe, LHCII has a similar liability to rubisco, but degradation of the protein was greatly reduced in tbe stay-green mutant. The light-harvesting complex of photosystem II is the major chlorophyll-binding membrane structure, and studies of its assembly and breakdown have revealed that pigments and apoproteins are mutually essential for survival of the holocomplex in vivo (Terao, Matsuoka & Katoh, 1988;Thomas et al, 1989). Not unexpectedly, therefore, chlorophyll and LHCII levels are usually highly correlated (Mae et al, 1993) and senescent leaf tissue of stay-green Phaseolus is no exception.…”
Section: Proteins During Senescence Of Stay-green and Normally Yellowmentioning
confidence: 99%
“…In the normal, yellowing genot\-pe, LHCII has a similar liability to rubisco, but degradation of the protein was greatly reduced in tbe stay-green mutant. The light-harvesting complex of photosystem II is the major chlorophyll-binding membrane structure, and studies of its assembly and breakdown have revealed that pigments and apoproteins are mutually essential for survival of the holocomplex in vivo (Terao, Matsuoka & Katoh, 1988;Thomas et al, 1989). Not unexpectedly, therefore, chlorophyll and LHCII levels are usually highly correlated (Mae et al, 1993) and senescent leaf tissue of stay-green Phaseolus is no exception.…”
Section: Proteins During Senescence Of Stay-green and Normally Yellowmentioning
confidence: 99%
“…The first step is dephytylation to give chlorophyllides and phaeophorbides. The intact tetrapyrrole ring system of chlorophyllide has been shown to be still associated with LHCP-2 (26). An ATP dependent opening of the macrocycle follows (M Schellenberg, Ph Matile, H Thomas, unpublished data).…”
Section: Discussionmentioning
confidence: 96%
“…The nongreen ultimate catabolites of Chl are absent from senescent leaves of Bf993 (14). The pattern of accumulation of intermediates in the degradative sequence points strongly to the ring-opening reaction as the site of the metabolic lesion in the nonyellowing mutant (26).…”
Section: Discussionmentioning
confidence: 98%
“…The dU2 and cyt-GI mutations may directly influence the turnover of the LHCBs. Alternatively, these mutations may indirectly influence LHCB accumulation by altering the turnover of nonprotein components of the thylakoid membranes; a similar model was proposed for the sid mutation in Festuca (Thomas et al, 1989;Nock et al, 1992).…”
Section: Discussionmentioning
confidence: 99%